Isosporan Oocysts in the Faeces of Bank Voles (Myodes glareolus; Arvicolinae, Rodentia): Real Parasites, or Pseudoparasites? - Trefancová, Aneta; Mácová, Anna; Kvičerová, Jana (Protist, 2019)
Coccidia of the genus Isospora, their origin, taxonomy, and host specificity have been discussed for many years. The crucial point in question being the division of the genus, based on distinct evolutionary history and the presence/absence of the Stieda body, into the genera Isospora (Eimeriidae) parasitizing mainly birds and reptiles, and Cystoisospora (Sarcocystidae) parasitizing mammals. The description of the majority of Isospora species from rodents is based solely on the oocysts found in their faeces. Some of them have been described with the presence of the Stieda body, some without it, and, simultaneously, for all the described species the molecular data are entirely lacking. This study reveals the origin of isosporan oocysts found in faeces of bank voles based on morphological analyses, phylogenetic analyses, and experimental infections. Morphological analyses showed the presence of the Stieda body complex on sporocysts. Phylogenetic analyses demonstrated close phylogenetic relationships between Isospora from bank voles and avian isosporans. Experimental inoculations of bank voles with sporulated oocysts of Isospora did not result in the production of unsporulated oocysts. Hence, these organisms should be considered pseudoparasites of the bank voles/rodents (probably originating from avian Isospora species).
Keywords: vole; feces; Phylogeny; pseudoparasite.; Female; coccidian; zvířata; Feces; ženské pohlaví; Male; Isospora; Cystoisospora; Arvicolinae; fylogeneze; Czech Republic; Oocysts; rodent; oocysty; Animals; Česká republika; mužské pohlaví